Pengembangan Media Video Untuk Perolehan Belajar Konsep Norma- Norma Kehidupan Pada Pelajaran Pedidikan Kewarganegaraan Di Kelas VII Mts Sirajul Ulum Pontianak - Marhani, - (Universitas Tanjungpura, 2016)
This study is a product development research which aims to produce media that explains neighbor norms in society. In this study involved a content expert, a media expert, fellow teachers, small group and large group trials. Subject trial is pebelajar class VII MTs SirajulUlum Pontianak. Data was obtained through interviews, observation and documentation. Analysis of the data using an interactive model of data collection, data presentation, data analysis and conclusion verification. Media development results validated by experts to ensure the quality of media produced. Tests performed on a small group trial and field trials. The results showed that the media used fit for use as a medium of learning. The average level of eligibility based on the expert content of 4.7% or excellent category; media expert validation 4.9% or very good, small group trial of 8.96% or excellent category; and field trials by 8.93% or excellent